1984
DOI: 10.1104/pp.74.2.385
|View full text |Cite
|
Sign up to set email alerts
|

Polyamine Biosynthetic Enzymes in the Cell Cycle of Chlorella

Abstract: During the life cycle of Chlorella vulgaris Beijerinck var vulgaris fa. vulgaris growing synchronously, the specific activity of ornithine decarboxylase peaked at the 2nd hour of the cycle, whereas that of arginine decarboxylase changed only slightly, increasing towards the end of the cycle. The endogenous level of putrescine and spermidine on a per cell basis increased gradually up to the 8th hour of the cycle, and declined thereafter. Thus, the peak of ornithine decarboxylase activity and the polyamine incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

1985
1985
2009
2009

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(20 citation statements)
references
References 23 publications
1
19
0
Order By: Relevance
“…1, 2). Nucleic acid levels in TX4 and TX 1 were also essentially identical (data not shown) and, as noted in other plant systems (12,13,25), a temporal correlation was observed between elevated polyamine content and nucleic acid production.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…1, 2). Nucleic acid levels in TX4 and TX 1 were also essentially identical (data not shown) and, as noted in other plant systems (12,13,25), a temporal correlation was observed between elevated polyamine content and nucleic acid production.…”
Section: Resultssupporting
confidence: 80%
“…Embryogenesis of carrot cells is associated with elevated polyamine levels and increased ADC activity (15,16). In contrast, ODC activity is more closely related to levels of DNA synthesis (13), as seen in the cell division phase in tomato ovaries following fertilization (1 1) and in meristematic tissues in tomato and potato (12).…”
Section: Resultsmentioning
confidence: 99%
“…This apparent contradiction may result from subcellular shifts in polyamine location that are reported to accompany various phases of cell division (9,31) and tissue development (1 1). The tobacco cultures that were analyzed had progressed beyond the stage ofrapid cell division and the accompanying demands for high levels of DNA synthesis but such cultures still contain cells at various stages ofgrowth and division.…”
Section: Resultsmentioning
confidence: 95%
“…This situation might explain why there have been so few reports in which significant growth inhibition has been shown to result from markedly decreased PA titers accomplished through the use of specific inhibitors of PA biosynthesis in vivo. Indeed, it has been reported that in log phase cultures of Chlorella grown in the presence of difluoromethylornithine, a significant increase in generation time is not observed until the second cell cycle, suggesting that endogenous PA titers are sufficient to support cell division and related biosynthetic activities for a considerable time (8).…”
Section: Discussionmentioning
confidence: 99%